2012
DOI: 10.1002/adem.201200129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Powder Size on Production Parameters and Properties of Syntactic Invar Foams Produced by Means of Metal Powder Injection Moulding

Abstract: Syntactic metal foams -a special foam type consisting of a metal matrix with integrated hollow elements like micro glass bubbles -offer an interesting spectrum of properties, like low densities, high capacity for crash energy absorption, vibration dampening capacity, and pressure-tightness. [1,2] For low melting matrix alloys infiltration techniques can be used for production, whereas for higher melting alloys other techniques are needed. Iron-based (e.g., pure Fe, FeNi2, FeCu3) micro-porous syntactic foam com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 1 publication
2
31
0
1
Order By: Relevance
“…For the latter, liquid metal processes have recently been reported, but usually powder metallurgy (PM) techniques are employed to limit processing temperatures. As porosity‐inducing particles, glass microspheres or ceramic macro‐ and microspheres are used . A special variant are all‐steel syntactic foams based on metallic hollow spheres and produced powder metallurgically, too.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…For the latter, liquid metal processes have recently been reported, but usually powder metallurgy (PM) techniques are employed to limit processing temperatures. As porosity‐inducing particles, glass microspheres or ceramic macro‐ and microspheres are used . A special variant are all‐steel syntactic foams based on metallic hollow spheres and produced powder metallurgically, too.…”
Section: Introductionmentioning
confidence: 82%
“…Experimental procedures closely follow the approach previously laid down by Weise et al, though with adapted process parameters reflecting the requirements of the new matrix. 5 µm 316L‐powder acquired from Sandvik Osprey was mixed with 50 vol% binder in a 400 mL Brabender mixer at 120°C.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the strain-rate sensitivity response at three different strain rate levels was studied by taking into account the influence of type and volume fraction of glass spheres. The materials' behaviour was found to be very similar to that of the metal matrix [2,[6][7][8]. Castro and Nutt produced steel based MMSFs, filled with ceramic hollow spheres by gravity fed and mechanical pressure infiltration.…”
Section: Introductionmentioning
confidence: 85%
“…MMSFs were developed for lightweight structures, requiring high strength and energy absorbing capacity [1]. The matrix material is usually an aluminium alloy (light and low cost), but nowadays high strength iron based matrices are also investigated [2][3][4][5][6][7][8][9][10][11]. As filler material, commercially available mixed-oxide ceramic [12][13][14][15], metallic [12] or SiC [16,17] hollow spheres are frequently applied, however Taherishargh et al have been made efforts for the application of low cost perlite filler as well [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…11) [64,65]. It was found that the compression stress-strain curve has a pronounced plateau regime; the plateau stress and plateau length depend on the added amount of glass hollow spheres.…”
Section: Powders With Placeholdersmentioning
confidence: 98%